Oracle® DBA SQL Quick Reference - Russel, Charlie; Cordingley, Robert (Pearson, 2003)
The Oracle SQL every DBA needs-fast and easy! Covers all the core day-to-day tasks DBAs are responsible for Quick access to SQL commands, operators, functions, data dictionary views, and more Includes dozens of easy-to-understand syntax diagrams The fast, practical Oracle SQL reference for every Oracle DBA! If you're a working Oracle DBA, here's the Oracle SQL reference you've been searching for-simple, straightforward, and incredibly easy to use! There's no faster way to discover the exact syntax you need ... refresh your memory about that option you haven't used lately ... find the name of that view you know exists ... start using that new Oracle 9 i feature you haven't tried yet. Keep it by your desk, near your server ... wherever you need fast, reliable answers right this minute! Covers Oracle SQL through Oracle9 i Release 2 Clear, well-organized tables of operators, functions, format models, privileges, and reserved words Complete command reference: syntax and options for every Oracle SQL command Standard "railroad" syntax diagrams make it easy to write correct syntax Handy listings of data dictionary views and dynamic performance tables